Study of Transuranium Recycling in PWR with 3-D Burnup Analysis using SRAC-COREBN Code - Abdul Waris; T. Rahmanto; Imam Taufiq; Rizal Kurniadi; Zaki Su’ud (Institut Teknologi Bandung, 2009)
In the light of proliferation resistance and terrorism issues several nuclear energy authorities and experts have suggested not to separate plutonium and minor actinides during the nuclear spent fuel reprocessing. Along the lines of this recommendation, a study of transuranium recycling in pressurized water reactor (PWR) with 3 dimensional burnup analysis by using SRAC-COREBN code has been carried out. The results show that by recycling of 8%, 10%, and 12 % of plutonium and minor actinides in PWR, the necessary uranium enrichment in loaded enriched uranium fuel of each scenario can be reduced to 2.7%, 1.52%, and 1.32%, correspondingly. In addition to this, the amount of loaded uranium fuel diminishes considerably with the increasing of the amount of recycled of plutonium and minor actinides.